ChemInform Abstract: Bimetallic Combinations for Dehalogenative Metalation Involving Organic Compounds. Issue 12 (25th March 2014) - Tilly, David; Chevallier, Floris; Mongin, Florence; Gros, Philippe C.
Abstract Review: 275 refs.